Serum Angiopoietin‐2 Predicts Mortality and Kidney Outcomes in Decompensated Cirrhosis. Issue 2 (4th January 2019) - Allegretti, Andrew S.; Vela Parada, Xavier; Ortiz, Guillermo A.; Long, Joshua; Krinsky, Scott; Zhao, Sophia; Fuchs, Bryan C.; Sojoodi, Mozhdeh; Zhang, Dongsheng; Karumanchi, S. Ananth; Kalim, Sahir; Nigwekar, Sagar U.; et al.
Abstract : Acute kidney injury in decompensated cirrhosis has limited therapeutic options, and novel mechanistic targets are urgently needed. Angiopoietin‐2 is a context‐specific antagonist of Tie2, a receptor that signals vascular quiescence. Considering the prominence of vascular destabilization in decompensated cirrhosis, we evaluated Angiopoietin‐2 to predict clinical outcomes. Serum Angiopoietin‐2 was measured serially in a prospective cohort of hospitalized patients with decompensated cirrhosis and acute kidney injury. Clinical characteristics and outcomes were examined over a 90‐day period and analyzed according to Angiopoietin‐2 levels. Primary outcome was 90‐day mortality. Our study included 191 inpatients (median Angiopoietin‐2 level 18.2 [interquartile range 11.8, 26.5] ng/mL). Median Model for End‐Stage Liver Disease (MELD) score was 23 [17, 30] and 90‐day mortality was 41%. Increased Angiopoietin‐2 levels were associated with increased mortality (died 21.9 [13.9, 30.3] ng/mL vs. alive 15.2 [9.8, 23.0] ng/mL; P  < 0.001), higher Acute Kidney Injury Network stage (stage I 13.4 [9.8, 20.1] ng/mL vs. stage II 20.0 [14.1, 26.2] ng/mL vs. stage III 21.9 [13.0, 29.5] ng/mL; P  = 0.002), and need for renal replacement therapy (16.5 [11.3, 23.6] ng/mL vs. 25.1 [13.3, 30.3] ng/mL; P  = 0.005). The association between Angiopoietin‐2 and mortality was significant in unadjusted and adjusted Cox regression models ( P  ≤ 0.001 for all models), and improved discrimination for mortality when added to MELD score (integrated discrimination increment 0.067; P  = 0.001). Conclusion : Angiopoietin‐2 was associated with mortality and other clinically relevant outcomes in a cohort of patients with decompensated cirrhosis with acute kidney injury. Further experimental study of Angiopoietin/Tie2 signaling is warranted to explore its potential mechanistic and therapeutic role in this population.